Characteristics of paleo-fluid of coal-bearing strata and its influence on the properties of CBM reservoirs in the Western Guizhou Province, China. Issue 4 (16th February 2016) - Xu, H.; Tang, D.-Z.; Li, S.; Tao, S.
ABSTRACT: The differential characteristics of paleo-fluids and their influence on the properties of coal reservoirs in Panxian and Zhijin areas were investigated by use of the data from experiments and drill wells. The results show that two generations of fluid activity related to hydrocarbon generation can be identified in these areas. The type of paleo-formation water indicates that the coal-bearing formation in Zhjin area is more favorable for hydrocarbon preservation than that of Panxian area. Under the influence of the paleo-fluid, the coal reservoirs in Zhijin area have poor pores connectivity, which are unfavorable to the output of coalbed methane.